Pengaruh Sertifikasi Halal dan Bauran Pemasaran Terhadap Intensi Pembelian Konsumen Muslim Pada Produk Minuman Kopi Kekinian - Mubarak, Rayhan Arfi; Arsyianti , Laily Dwi; Hasanah , Nur (Institut Pertanian Bogor, 2023)
This research aims to analyze the influence of the halal label on the intention to purchase contemporary coffee labeled halal in Indonesia and analyze the influence of the marketing mix (product, price, place, promotion) on the intention to purchase contemporary coffee labeled halal in Indonesia. . This research was conducted on consumers who were at least 20 years old, Muslim and had purchased and were interested in consuming contemporary coffee products that were halal certified. with a total of 110 respondents using purposive sampling. The aim of this research is to analyze the influence of halal labeling on interest in buying contemporary coffee labeled halal in Indonesia, analyze the influence of the marketing mix (product, price, place, promotion) on interest in buying contemporary coffee labeled halal in Indonesia and analyze what strategies can be implemented to increase Interest in contemporary halal certified coffee products. Data collection was carried out by filling out an online questionnaire. The statistical analysis used is the PLS Structural Equation Model (SEM). The results of this research show that the influence of the halal label has a positive and significant relationship with the intention to buy contemporary coffee and shows that the marketing mix consisting of product, place and promotion variables has a positive and significant relationship with the intention to purchase contemporary coffee, while the price variable has a negative effect. and negative. does not have a significant effect on interest in buying contemporary coffee. This is because the good quality of service, place and product means that consumers do not consider the current price of coffee.